Psychological Difficulties Mediate and Self-Efficacy Moderates the Relationship Between Family Cumulative Risk and Hope Among Chinese Children From Low-Income Families - Yin, Xiayun; Wang, Dongfang; Li, Zhihua; Huang, Yuesheng (Frontiers in Psychology, 2021)
This longitudinal study investigated the role of psychological difficulties and self-efficacy in the relationship between family cumulative risk and hope among children from low-income families. The participants were 392 Chinese children from low-income families; the study extended for two years, and participants completed data were collected with the following questionnaires: the Family Cumulative Risk Index, Children’s Hope Scale, Strengths and Difficulties Questionnaire-Difficulties subscale, and General Self-efficacy Scale. The results demonstrated that psychological difficulties played a mediating role in the relationship between family cumulative risk and hope; specifically, family cumulative risk predicted children’s hope via psychological difficulties. Self-efficacy moderated the relationship between psychological difficulties and hope. This moderation supported “a drop in the ocean effect;” the protective effect of high self-efficacy worked only when psychological difficulties were at low levels. When psychological difficulties were at high levels, the buffering effect of self-efficacy on family cumulative risk was gradually weakened and eventually lost.